Microimenópteros de Musca domestica L. (Diptera: Muscidae) coletados em diferentes substratos em Itumbiara, Goiás Microhimenopterous of Musca domestica L. (Diptera: Muscidae) collected in different substrata in Itumbiara, Goias - C.H. Marchiori (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2006)
The species of parasitoids associated with Musca domestica L. (Diptera: Muscidae) collected in human feces, cattle liver, chicken viscera, cattle dung, chicken manure and food leftovers in Itumbiara, State of Goiás, Brazil, from July 1999 to July 2003, were studied. The pupae were obtained by the flotation method. They were individually placed in gelatin capsules until the emergence of the adult flies or their parasitoids. The overall prevalence of parasitism was 0.7%. The most frequent species was Pachycrepoideus vindemiae (Rondani) (Hymenoptera: Pteromalidae), accounting for 35.4%.